Daflon and Centrum mitigate vancomycin-induced nephrotoxicity in rats by ameliorating oxidative stress, DNA damage, apoptosis, and inflammation - El-Gendy, Hanem F.; Salamah, Soaad; Elhusseiny, Eman; Khalifa, Hazim O.; El-Banna, Hossny A.; Attia, Taha A.; Selim, Shaimaa; Hanbally, Saber El (Frontiers in Toxicology, 2025)
BackgroundVancomycin (VM) is widely used for treating life-threatening infections caused by Gram-positive bacteria resistant to other antibiotics. However, its nephrotoxic effects limit clinical use.ObjectiveThis study aimed to evaluate the protective effects of Daflon (DF) and Centrum (CE) against VM-induced nephrotoxicity in male rats.MethodsFifty healthy male Wistar rats were randomly divided into five groups. Group 1 (negative control) received saline intraperitoneally (IP) for 7 days followed by oral distilled water for 7 days. Group 2 (positive control) received VM (400 mg/kg BW, IP) for 7 days. Group 3 received VM for 7 days followed by DF (100 mg/kg BW, oral) for 7 days. Group 4 received VM for 7 days followed by CE (15 mg/kg BW, oral) for 7 days. Group 5 received VM for 7 days followed by combined DF and CE treatment for 7 days. Blood and kidney samples were collected for hematological, biochemical, molecular, comet assay, and histopathological evaluations.ResultsVM administration significantly elevated serum creatinine, urea, and uric acid levels (p < 0.01), increased renal malondialdehyde (MDA), and reduced catalase (CAT) and superoxide dismutase (SOD) activities (p < 0.05). It also induced marked histological changes and increased DNA fragmentation. DF and CE, particularly in combination (Group 5), significantly reduced renal injury, DNA fragmentation, and histopathological alterations. The protective effect followed the order: G5 > G4 > G3 > G2. Furthermore, VM upregulated PARP1, RIP1, KIM1, TNF-α, and IL-1β expression, which were markedly downregulated by DF and CE.ConclusionDF and CE attenuated VM-induced nephrotoxicity through antioxidant, anti-inflammatory, and DNA-protective mechanisms. Their combination provided superior renal protection by reducing oxidative stress, inflammation, and apoptosis, while enhancing antioxidant defenses and DNA repair capacity.